Poverty in Mexico in the 1990s - Jesus Manuel Salas (Luxembourg Income Study (LIS), 2003)
This paper explores poverty trends in Mexico during the 1990's using three different definitions of poverty. The paper then uses poverty convergence analysis to explore the pre-crisis (1992-1994), the crisis (1994-1996), and the recovery periods (1996-1998). Finally, the paper incorporates a regional analysis in order to examine these poverty effects in greater detail.
Keywords: 330; Armut; Armutsbekämpfung; Regionale Disparität; Mexiko